Sarmentosamide, an Anti-Aging Compound from a Marine-Derived Streptomyces sp. APmarine042 - Eun-Soo Lee; Eun-Young Lee; Jisoo Yoon; Ahreum Hong; Sang-Jip Nam; Jaeyoung Ko (Marine Drugs, 2020)
Many bioactive materials have been isolated from marine microorganisms, including alkaloids, peptides, lipids, mycosporine-like amino acids, glycosides, and isoprenoids. Some of these compounds have great potential in the cosmetic industry due to their photo-protective, anti-aging, and anti-oxidant activities. In this study, sarmentosamide (1) was isolated from marine-derived Streptomyces sp. APmarine042, after which its capacity to decrease skin aging was examined in-vitro. Sarmentosamide (1) was found to significantly reduce UVB-induced matrix metalloproteinase-1 (MMP-1) expression in normal human dermal fibroblasts (NHDFs) by inhibiting the extracellular signal-regulated kinase (ERK) and the c-Jun N-terminal kinase (JNK) phosphorylation, which are regulatory pathways upstream of MMP-1 transcription. Additionally, we confirmed that sarmentosamide (1) decreased tumor necrosis factor-alpha (TNF-α), induced MMP-1 secretion in NHDFs, and exhibited free-radical scavenging activity, as demonstrated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Therefore, our study suggests that sarmentosamide (1) could be a promising anti-aging agent that acts via the downregulation of MMP-1 expression.